Prolactin receptor expression in mouse dorsal root ganglia neuronal subtypes is sex‐dependent. (4th July 2019) - Patil, Mayur; Hovhannisyan, Anahit H.; Wangzhou, Andi; Mecklenburg, Jennifer; Koek, Wouter; Goffin, Vincent; Grattan, David; Boehm, Ulrich; Dussor, Gregory; Price, Theodore J.; Akopian, Armen N.
Abstract: Sensory neurones exhibit sex‐dependent responsiveness to prolactin (PRL). This could contribute to sexual dimorphism in pathological pain conditions. The present study aimed to determine the mechanisms underlying sex‐dependent PRL sensitivity in sensory neurones. A quantitative reverse transcriptase‐polymerase chain reaction shows that prolactin receptor (Prlr) long and short isoform mRNAs are expressed at comparable levels in female and male mouse dorsal root ganglia (DRG). In Prlr cre/+ ;Rosa26 LSL‐tDTomato/+ reporter mice, percentages of Prlr + sensory neurones in female and male DRG are also similar. Characterisation of Prlr + DRG neurones using immunohistochemistry and electrophysiology revealed that Prlr + DRG neurones are mainly peptidergic nociceptors in females and males. However, sensory neurone type‐dependent expression of Prlr is sex dimorphic. Thus, Prlr + populations fell into three small‐ and two medium‐large‐sized sensory neuronal groups. Prlr + DRG neurones are predominantly medium‐large sized in males and are proportionally more comprised of small‐sized sensory neurones in females. Specifically, Prlr + /IB4 + /CGRP + neurones are four‐ to five‐fold higher in numbers in female DRG. By contrast, Prlr + /IB4 − /CGRP + /5HT3a + /NPYR2 − are predominant in male DRG. Prlr + /IB4 − /CGRP −, Prlr + /IB4 − /CGRP + and Prlr + /IB4 − /CGRP + /NPYR2 + neurones are evenly encountered in female and male DRG. These differences were confirmed using an independently generated single‐cell sequencing dataset. Overall, we propose a novel mechanism by which sensory neurone type‐dependent expression of Prlr could explain the unique sex dimorphism in responsiveness of nociceptors to PRL.